You are on page 1of 28

# (Effective Alternative Secondary Education)

MATHEMATICS II
Y

MODULE 2

BUREAU OF SECONDARY EDUCATION
Department of Education
DepEd Complex, Meralco Avenue, Pasig City

Module 2
This module is about quadratic equations. This is a continuation of the
previous module. In this module you will learn two more methods of solving
quadratic equations. You have to be proficient in the square root method of
solving quadratic equations in order to understand the two methods to be
discussed. As you go over the exercises, you will develop skills in solving
quadratic equations and eventually use these skills in solving problems.

## What you are expected to learn

This module is designed for you to:
1. Solve quadratic equations by completing the square.

## How much do you know

A. Solve the following by completing the square:
1. x - 8x - 15 = 0
2. x - 2x - 7 = 0
3. x + 3x = 1
4. x +

2
x=0
3

5. 6t - 5t = t + 3t 1
B. Solve the following by the quadratic formula.
1.
2.
3.
4.
5.

x - x 12 = 0
x -4x = 0
3x + 2 = 0
3x - x = 1
x = 1 2x

## What you will do

Lesson 1
Completing the Square
Completing the square is a method used to make a quadratic expression a
perfect square trinomial. This method is used to solve quadratic equations which
cannot be solved by factoring.
The method of completing the square is based on the special product:
x2 + 2px + p2 = (x + p)2
x2 + 2px + p2 is a perfect square trinomial because it is the product of (x +
p) , the square of a binomial. In this trinomial, notice that if you take one-half the
coefficient of the x in the middle term and square it, you get the third term.
2

x2 + 2bx + b2

1
(2b)2 = (b)2 = b2
2

## Therefore, to make an expression such as x 2 + 12x into a perfect square

trinomial, you must take one-half of 12, square it and add it to x 2 + 12x.
If you follow the procedure, here is how it is done.
x2 + 12x

x2 + 12x + ________

1
(12)2 = (6)2 = 36
2

x2 + 12x + 36
Hence, x + 12x + 36 is now a perfect square trinomial which when
factored as (x + 6)(x + 6) can also be written as (x + 6) 2.
Lets look at some more examples:
Examples:
Complete the square of the following expressions:
a) x2 + 4x

b) x2 - 6x

c) x2 - 5x

d) 2x2 - 3x

a) x2 + 4x
Solution:
x2 + 4x + ______

## The coefficient of the x term is 4.

1
(4)2
2

x2 + 4x +

Take

x2 + 4x + (2)2

1
of 4 or divide 4 by 2.
2

Square 2.

x2 + 4x + 4
Note that x2 + 4x + 4 = (x + 2)2
b) x2 - 6x
Solution:
x2 - 6x + ______
x2 - 6x +

## The coefficient of the x term is -6.

1
(-6)2
2

1
of -6 is -3
2

x2 6x + (-3)2

Square -3

x2 - 6x + 9
Note that x - 6x + 9 = (x - 3)2
c) x2 - 5x
Solution:
x2 - 5x + _______

Note that

## The coefficient of the x term is -5

x2 - 5x +

1
(-5)2
2

1
5
of -5 is
2
2

x2 5x + (

5 2
)
2

Square

x2 - 5x +

25
4

x2 - 5x +

5
2

25
5 2
= (x )
4
2

You will notice that the leading coefficient in the first three examples is 1. So,
before proceeding to completing the square, transform the leading coefficient to
1. The leading coefficient of the next example is not equal to 1.

d) 2x2 - 3x
Solution:

2x2 - 3x

Note that x2

x2

3
x + _____
2

x2

3
1 3
x + (- )2
2
2 2

x2

3
3
x + - 2
2
4

x2

3
9
x+
2
4

1
3
3
of is 2
2
4

Square -

3
4

3
9
3 2
x+
= (x )
2
4
2

## Try this out

Find the third term to be added to make each expression a perfect square
trinomial. Write the result as a square of a binomial.
A.
1.
2.
3.
4.
5.

x2
x2
x2
x2
x2

+ 4x
+ 6x
- 10x
- 8x
+ 12x

B.
1. x2 + x
2. a2 3a
3. b2 - 13b
4. b +
5. c -

2
b
3
5
c
2

C.
1.
2.
3.
4.

2x2
3x2
3x2
4x2

+ 4x
- 6x
-x
- 3x

5.

5x2 + 2x

Lesson 2
Solution of Quadratic Equations by Completing the Square
You are now ready to solve equations by completing the square. In this
method, the left-hand side of a quadratic equation is solved by completing the
square so that it becomes a perfect square trinomial which can be written in the
form (x + p)2 = d.
Example 1: Solve by completing the square:
x2 + 8x 5 = 0
Solution: Note that the left member of the equation x 2 + 8x 5 = 0 is not a perfect
trinomial square. Separate -5 from the left member by adding +5 to
both sides of the equation.
x2 + 8x 5 = 0
You now have x + 8x on the left-hand side of the equation. Now, make
the left-hand side a perfect square trinomial. You can do this by adding the
square of one-half of the coefficient of x. So that,
x2 + 8x +

1
(8)2 .
2

1
of 8 is 4.
2

x2 + 8x + (4)2

Square 4.

Since you have done the first part in completing the square of the left
member of the equation, go back to the original equation.
Since (4)2 or 16 is added to the
left member, (4)2 or 16 must also
be added to the right member by

x2 + 8x = 5
x2 + 8x + (4)2 = 5 + (4)2
x2 + 8x + 16 = 5 + 16
(x + 4)2 = 21

## The equation is now of the form (x + p) 2 = d, and so the square root

method may then be used. Thus,
(x+4)2 = 21

x+4 = 21

## Taking the square root

x = -4 21

Subtracting

on

both

sides
x = -4 + 21 or x = -4 - 21
The solutions are -4 + 21 and -4 - 21 .
Check::
If x = -4 +

21

x + 8x 5 = 0
0 = x + 8x - 5
= (-4 +

21 ) + 8(-4 +

21 ) 5

= 16 - 8 21 + ( 21 ) - 32 + 8 21 5
= 16 + 21 32 5
= 37 37
=0
If x = -4 -

21

x + 8x 5 = 0
0 = x + 8x - 5
= (-4 -

21 ) + 8(-4 -

21 ) 5

= 16 + 8 21 + ( 21 ) - 32 - 8 21 5
= 16 + 21 32 5
= 37 37
=0
The solutions check.
Example 2: Solve by completing the square.
4x2 + 4x - 3 = 0
Solution: Notice that the coefficient of x is not 1. You need to make the
coefficient of x equal to 1 first before you attempt to use
completing the square. Follow the steps on the right.

4x2 + 4x - 3 = 0
x2 + x -

3
4

=0

x2 + x =
x2 + x +

## Divide both sides by 4

3
4

1
1
3
(1)2 =
+ (1)2
4
2
2

x2 +x +

3
to both sides
4
1
(1)2 to both sides
2

3
1
1
=
+
4
4
4

(x +

1 2
) =1
2

x +

1
=
2

x+

1
=1
2

Factor
Use square root method

x = -

1
1
2

x = -

1
+1
2

x = -

1
-1
2

x =

1
2

x = -

3
2

## Note that this equation can be solved by factoring:

4x2 + 4x - 3 = 0
(2x 1)(2x + 3) = 0
2x 1 = 0
2x = 1
1
x=
2

or

2x + 3 = 0
2x = -3
3
x=2

Check:
If x =

1
2

4x2 + 4x - 3 = 0
4(

1
1
) + 4( ) 3 = 0
2
2

4(

1
4
)+
3=0
2
4

1+23=0
33=0
0=0
If x = -

3
2

4x2 + 4x - 3 = 0
4(-

3
3
) + 4(- ) 3 = 0
2
2

4(

9
12
)
3=0
4
2

963=0
33=0
Both solutions check.
Example 3:
Solve by completing the square:
2x2 - 5x 3 = 0
Solution:

## Again, just like Example 2, you need to make the coefficient of

x equal to 1. Divide both sides of the equation by 2 to make
the coefficient of x equal to 1. Then proceed as follows:
2x2 - 5x 3 = 0
x2

5
3
x
=0
2
2

x2
x2

5
3
x =
2
2

## Add 3/2 to both sides

5
1 5
3
1 5
x + (- )2 =
+ (- )2 Add 1 (- 5 )2 to both sides
2
2 2
2
2 2
2 2

x2

5
5
3
5
x + - 2 =
+ - 2
2
4
2
4

x2

5
25
3
25
x+
=
+
2
16
2
16

(x

5 2
24
) =
4
16

Simplify
Factor the left-hand side & get the
LCD of the right-hand side of the
equation.

25
16

5 2
49
) =
4
16

(x

5 2
) =
4

(x
x

5
4

x =

x=

49
16

7
4

5
7

4
4

5
7
+
4
4

x =

Solve for x

and

x =

12
4

5
7
4
4

x=-

x=3

x=-

5
to both sides.
2

2
4

1
2

1
.
2

## Note that this equation can also be solved by factoring:

2x - 5x 3 = 0
( 2x + 1 )( x 3 ) = 0
2x + 1 = 0

or

x3=0

2x = -1
x=-

x=3

1
2

Check:
If x = -

1
2

2x - 5x 3 = 0
2(-

1
1
) - 5(- ) 3 = 0
2
2

2(

1
5
)+
3 = 0
4
2

1
5
6
+

=0
2
2
2
6
6

=0
2
2

0=0

10

If x = 3

2x - 5x 3 = 0
2(3) - 5(3) 3 = 0
2(9) + 15 3 = 0
18 + 15 3 = 0
33=0
0=0

## The solutions check.

Example 4:
Use completing the square to solve equation:
-x -2x + 3 = 0
Solution:

## In this equation, note that the coefficient of x is 1. This

means that you just cannot apply completing the square right
away. You need to make the coefficient of x equal to 1. To do
this, multiply both sides of the equation by 1. Thus,
-1(-x - 2x + 3) = 0(-1)
x + 2x 3 = 0
x + 2x +

1
1
(2)2 = 3 + (2)2
2
2

x + 2x + 1 = 3 + 1
(x + 1) = 4
x+1= 4
x = -1 2
x = -1 + 2
or
x=1

Solve for x

x = -1 2
or
x = -3

## The solutions are 1 and -3.

Note that the equation can be solved by factoring.
-x -2x + 3 = 0
-(x + 2x 3) = 0
x + 2x 3 = 0
(x + 3)(x 1) = 0
x+3=0

or

11

x1=0

x = -3
Check::
If x = -3

or

x=1

-x -2x + 3 = 0
-(-3) - 2(-3) + 3 = 0
-(9) + 6 +3 = 0
-9 + 9 = 0
0=0

If x = 1

-x -2x + 3 = 0
-(1) - 2(1) + 3 = 0
-1 2 +3 = 0
-3 + 3 = 0
0=0

## The solutions check.

Example 5:
Use completing the square to solve equation:
-2x2 - 4x +2 = 0.
Solution: This equation cannot be solved by factoring.
-2x2 -4x +2 = 0
x2 +2x -1 = 0

x2 + 2x

## Add 1 to both sides

x2 + 2x+

=0

1
1
(2)2 = 1 + (2)2
2
2

1
(2)2 to both sides to
2

x + 2x +1 = 1+ 1
(x + 1 )2 = 2
x + 1=
x = -1
x = -1+ 2

2

method
Solve for x

and

x = -1 -

## The solutions are -1+ 2 and -1+ 2 .

12

Check:
If x = -1+ 2

-2x2 - 4x + 2 = 0

-2(-1+ 2 ) - 4(-1+ 2 ) + 2 = 0
-21 - 2 2 + ( 2 ) + 4 - 4 2 + 2 = 0
-2 + 4 2 - 2(2) + 4 - 4 2 + 2 = 0
-2 - 4 + 4 + 2 = 0
-6 + 6 = 0
0=0
If x = -1 -

-2(-1 -

-2x2 - 4x + 2 = 0
2 ) - 4(-1 -

2)+2=0

-21 + 2 2 + ( 2 ) + 4 + 4 2 + 2 = 0
-2 - 4 2 - 2(2) + 4 + 4 2 + 2 = 0
-2 4 + 4 + 2 = 0
-6 + 6 = 0
0=0
Both solutions check.
From the preceding examples, you must be able to identify the steps in
solving quadratic equations by completing the square method.
To solve an equation by completing the square, follow these steps:
1. Make sure that coefficient of x2 is 1. If it is not, make it 1 by dividing both
sides of the equation by the coefficient of x2.
2. Isolate the constant (numerical term) by transposing it on the right-hand
side of the equation.
3. Complete the square:
a) Identify the coefficient of x.
b) Take half the coefficient of x.
c) Square half the coefficient of x
d) Add the numbers in c to both sides of the equation
4. Factor the left side and simplify the right sides of the equation.
5. Solve the resulting equation by square root method.
6. Check the solution.

13

## Try this out

Solve the following by completing the square.
For Nos. 1 15, see Example 1
1. x2 + 8x + 6 = 0
2. x2 4x 3 = 0
3. x2 10x = 15
4. u2 5u 2 = 0
5. x2 6x = 19
6. a2 4a 5 = 0
7. x2 + 10x + 20 = 0
8. x -2x 5 = 0
9. a - 8a 20 = 0
10. z + 5 = 7z
11. x + 8x 9 = 0
12. x + 6x 7 = 0
13. x + 6x + 8 = 0
14. x + 5x 6 = 0
15. x = 4x + 3
For Nos. 16 20, see Examples 2 and 3
16. 2x2 = a 4x
17. 3x2 = 12 6x
18. 3x = 2 5x
19. 2x = 5x + 3
20. 4x = 2 7x
For Nos. 21 25, see Examples 4 and 5
21. x - 12x = 6
22. -2z + 12z 4 = 0
23. 2x(x + 3) = 8
24. x(x + 3) -1/2 = -2
25. 20x - 11x 3 = 0
14

Lesson 3
In this lesson, you will see how completing the square will be used to
derive the Quadratic Formula. This method works easily in solving any quadratic
equation.
To do this, let us begin with solving a Quadratic Equation of the form ax 2 +
bx + c = 0 by completing the square.
Example 1

Solution:
2x2 + 7x + 4 = 0
7
x+2=0
2

x2 +

eqn by 2
x2 +

7
x =-2
2

## Add -2 to both sides of the eqn

1
7
the square of
of
.
7
1
7
1
7
2
2
x2 + x + ( )2 = -2 + ( )2
2
2 2
2 2

x2 +

7
49
49
x+
= -2 +
2
16
16
7 2
32
49
(x +
) = +
4
16
16

(x +

## Factor the left-hand side and

simplify the right hand side by
finding the LCD, which is 16.

7 2
17
) =
4
16

x+

7
4

x+

7
=
4

x=-

## By the square root method

17
16
17
4

Solve for x.
17
4

15

7 17
4

x=

and

x=

7 17
4

Now, study the following derivation of the quadratic formula by the method
of completing the square. The steps is just like what has been done in Example 1
so that you can see that the process is the same. The only difference is that you
will be working with letters instead of numbers.
ax2 +bx + c = 0
x2 +

b
c
x+
=0
a
a

x2 +
x2 +

## Divide both sides by a.

b
c
x =a
a

Subtract

b
1 b
c
1 b
x + ( )2 = + ( )2
a
2 a
a
2 a

b
b2
x2 +
x+
a
4a 2

c
b2
= +
a
4a 2

b 2 4ac
4a 2

b
=
2a

b 2 4ac
2a

x+

x=-

or

x=

2a

## Solve the equation by the

square root method
(5)
Solve for x.

b 2 4ac
2a

b b 2 4ac
2a

x=

b
1
of
.
2
a

## Factor the left-hand side and

simplify the right-hand side
by finding to LCD which is
4a.

b 2
4ac b 2
(x +
) =
2a
4a 2

b
x+
=
2a

c
from both sides.
a

b b 2 4ac
2a

16

The quadratic formula tells you that if you have a quadratic equation in standard
form ax2 + bx + c =0, then all you have to do is substitute the values of a, b and c
into the formula to get the solutions.
Example 2
Solve by using the quadratic formula
x2 - 3x - 5 =0
Solution:

## The equation is already in standard formula. To use the

formula you must first identify a, b, and c.
a=1

b = -3

c = -5

## Substituting these values into the formula, you should get

b b 2 4ac
2a

x=

( 3) (3) 2 4(1)(5)
2(1)

3 9 20
2

=
The solution are

29
2

29
2

and

29
2

Check:
If x =

29

x2 - 3x - 5 = 0

29
2

) - 3(

29
2

)-5=0

9 3 29
9 6 29 ( 29) 2
5=0
4
2
17

2(9 3 29)
9 6 29 ( 29) 2
5=0
4
4
9 6 29 29 18 6 29
-5=0
4

20
-5=0
4

5-5=0
0=0
If x =

29

x2 - 3x - 5 = 0

29
2

) - 3(

29
2

)-5=0

9 3 29
9 6 29 ( 29) 2
5=0
4
2
2(9 3 29)
9 6 29 ( 29) 2
5=0
4
4
9 6 29 29 18 6 29
-5=0
4

20
-5=0
4

5-5=0
0=0
You may find that checking is a little bit tedious but its fun doing since you
get to apply your skills in simple arithmetic.
Notice that the quadratic formula is a lot easier to use than completing the
square. This is because the formula contains all the steps necessary if you were
using completing the square.
Here are some things to watch out when using the Quadratic Formula:
1. If b is positive, then the b that appear in the formula will be
negative. If b is negative, then the value of b in the formula will be
positive.
2. The quantity 2a in the formula is the denominator of the entire
expression -b b 2 4ac .

18

Example 3:
Solve by using the quadratic formula
3x2 3x =5
Solution:

## Begin by writing the equation into the standard form

3x2 +11x = 4
3x2 + 11x - 4 = 0

a=3
x=

b = 11

c = -4

b b 2 4ac
2a

Then we have,
x =

11

(11) 4(3)(4)
2(3)

11 121 ( 48)
6

11 169
6

x =

11 13
6

x=

11 13
and
6

x=

2
1
=
6
3

The solution is

x=

11 13
6

24
= -4
6

1
and -4.
3

## The checking is left for you.

Example 4
19

3 2t = t2
Solution: Arrange the equation in standard form and identify a, b, and c.
t2 + 2t - 3 = 0
a=1

b=2

c = -3

t=
t=

b b 2 4ac
2a
( 2)

t=
=
t=
t=
=

24
2

( 2) 2 4(1)( 3)
2(1)

4 12
2

2 16
2

24
2
and

2
2

t=
=

t=1

24
2
6
2

t = -3

## The solution are 1 and -3.

This equation can be solved by factoring. Try solving and check..
Example 5
Solve for x :

2x2 5x + 7 = x(2x - 3)

Solution: Be careful! This does not mean that just because there is an x 2
in the equation that the equation 2x2 5x + 7 = x(2x - 3) must
Putting the equation in standard form, then

20

2x2 5x + 7 = x(2x- 3)
2x2 5x + 7 = 2x2 - 3x
- 2x2 + 3x
-2x2 + 3x
-2x + 7 = 0
-2x = -7
x =

7
2

As you can see, its not a quadratic equation at all. Example 5 clearly
shows, the method of solving an equation depends on the type of equation you
are dealing with. Look carefully at the equation before deciding the method to
apply.
Example 6
x2 + 3x+ 4 =0
Solution:

a=1
x=
x=
=
x=

b=3

c=4

b b 2 4ac
2a
3

(3) 2 4(1)(4)
2(1)

9 16
2

3 7
2

## Not real solution

As soon as you see that the answer involves the square root of a negative
number, you can stop and say that the equation has no real solution.

## Try this out

A. Write each equation in standard form, if necessary. Then, determine the
values of a, b and c. Do not solve the equation.

21

1. x + 4x + 3 = 0
2. x - x 4 = 0
3. 3x - 2x + 7 =0
4. 4x + 7x 3 = 0
5. 4y = 2y 1
6. 2x = 3x + 4
7. x(3x 5) = 2
8. y(5y + 10) = 8
Solve the equations using the Quadratic Formula.
B.

1. x2 + 3x - 5 =0
2. x2 + 5x - 2 =0
3. y2 + 4y - 6 =0
4. y2 + 2y - 5 =0
5. u2 2u + 3 =0
6. u2 - 3u + 3 =0
7. t2 - 7t = 6
8. t2 + 6 = 6t

C.
1.
2.
3.
4.
5.
6.
7.

5x2 - x = 2
7x2 - 3 = x
3x2 + 5x + 2 =0
2x2 - 3x - 1 =0
t2 - 3t + 4 = 2t2 + 4t - 3
(5w + 2) (w - 1) = 3w + 1
(x + 2)2 = x(x + 4)

## D. Find out what is wrong with the following solution:

x - 3x 1 = 0
x=
x=
=

b b 2 4ac
2a
3

94
2

3
2

Lets Summarize
1. Most types of quadratic equations can be solved by completing the square.
2. In completing the square, it is important to remember that
22

## a. the coefficient of x2 should be 1; if not, divide both sides of the equation

by the coefficient of x2.
b. the term to be added is the square of one-half the coefficient of x in the
equation.
x=

b b 2 4ac
2a

## What have you learned

A. Solve by completing the square:
1.
2.
3.
4.
5.

x - 4x 2 = 0
x - 2x 4 = 0
x + 2x = 0
6(x - 1) = 5x
(x + 2)2 4x = 8

## B. Solve using the quadratic formula:

1.
2.
3.
4.
5.

x + 6x + 9 = 0
x -4x = 0
x - 7 = 0
x + 8x + 12 = 0
2x + x = 5

23

How much do you know
A.

B.

1.

31

2.

3.

3 13
2

4.

0, -

5.

4 11
5

1.

4, -3

2.

0, 4

3.

no real solution

2
3

4.

or 1 2 2

13
6

5.

-1

## Try this out

Lesson 1
A. 1. 4, (x + 2)2
2. 9, (x + 3)2
3. 25, (x - 5)2
4. 16, (x - 4)2
5. 36, (x + 6)2
B. 1.

1
1 2
, (x +
)
2
4

2.

9
3 2
, (a )
4
2

3.

169
13 2
, (b )
4
2

24

4.

1
1 2
, (b +
)
9
3

5.

25
5 2
, (c )
16
4

C. 1. 1, (x + 1)2
2. 1, (x - 1)2
3.

1
1 2
, (x )
36
6

4.

9
3 2
, (x )
64
8

5.

1
5

1 2
)
25

, (x -

Lesson 2
B. 1. 4

10

2. 2

3. 5

40

33

4.

or 5 2

10

5. 3

28

or 3 2

6. 5, -1
7. -5

8. 1

9. 10, -2
10.

29
2

11. -9, 1
12. -7, 1
13. -2, -4
14. 1, -6
15. 2

16. -1

17. -1 /5

25

18. -2,

1
3

19. 3, -

1
2

20. -2,

1
4

21. -6

30

22. 3

23. -4, 1
24.

3
2

25. , 1/5
Lesson 3
A.
1.

SF

a=1

b=4

c=3

2.

SF

a=1

b = -1

c = -4

3.

SF

a=3

b = -2

c=7

4.

SF

a=4

b=7

c = -3

5.

## 4y2 -2y + 1=0

a=4

b = -2

c=1

6.

3x2-2x +4 =0

a=3

b = -2

c=4

7.

3x2 -5x -2 = 0

a=3

b = -5

c = -2

8.

5y2 + 18y- 8 =0

a=5

b = 10

c = -8

B.
1.

3 29
2

2.

5 33
2

3.

4. -1

10
6

5. no real solution
6. no real solution
7.

73
2

26

8. 3

C.
1.

1 41
10

2.

1 85
14

3. no real solution
4.

3 17
4

5.

7 77
2

6.

6 96
3 2 6
or
10
5

7. no real solution
D. The solution should be:
x - 3x 1 = 0
x=

b b 2 4ac
2a

x=

3 9 4
2

3 13
2

A.

1. 2

2. 1

3. -2, 0
4.

3
2
,2
3

5. 2
B.

1. -3

27

2. 4, 0
3.

4. -2, -6
5.

1 41
4

28